AB0616 Adaptation into spanish of The Hand Mobility in Systemic Sclerosis Test (Hamis) in A Group of Patients with Systemic Sclerosis. (15th July 2016) - Mayer, M.M.; Alsina, G.; Maldonado Cocco, J.A.; Rivero, M.; Lara, M.E.; Maldonado Alsina, P.; Gallacher, A.; Khoury, M.; Earsman, G.; Barreira, J.C.
Abstract : Background: Hand function in scleroderma patients can be assessed by specific instruments such as the Cochin scale and the Scleroderma Health assessment questionnaire (SHAQ), both self administrated. Sanqvist and Eklun designed the Hand Mobility in Systemic Sclerosis test (HAMIS), which is performed by the evaluation of a health professional. The original instrument was designed in English. Objectives: The aim of this study was to adapt into Spanish the HAMIS test in order to assess hand function in patients with systemic sclerosis and to evaluate its reliability and validity. Methods: The study included 28 patients that met ACR/EULAR 2013 classification criteria for systemic sclerosis, who attended the Rheumatology Service from March 2014 to March 2015; 21 were diffuse and 7 limited. Patients with overlapping and sclerodermiform syndromes were excluded. Demographic data, clinical manifestations, laboratory studies including ANA by IIF (Hep2) were recorded. Different scores were performed: modified Rodnan, Medsger and Cochin. HAMIS was translated into Spanish and back translated into English. Four translators did not know the original English version of the test. A pilot test was conducted in 5 systemic sclerosis patients and adaptations were performed in order to obtain the final Spanish version. HAMIS test was assessed by an occupational therapist. Two weeks later, the study was repeated in 10 patients chosen randomly to assess stability (test-retest) and concordance according to Bland&Altman. Values of HAMIS and Cochin test were correlated (Spearman's Rank correlation coefficient). Results: All 28 patients (27 female) had mean age at diagnosis of 49.6±13 years and median disease duration of 5 years (range=0–25). All patients developed Raynaud's phenomenon (mean age at onset of Raynaud of 45±17 years), 3 patients had puffy hands, 11 presented digital ulcers, 9 pitting scars and 23 telangiectasia. Through capillaroscopic evaluation, early pattern was found in 11 patients, active in 7 and late in 8 patients. When analyzing severity by Medsger score, such was normal in 1 patient, 11 presented mild involvement, 13 moderate and 3 severe. Median for Rodnan score was of 6 (range=2–27) and 8 for Cochin (range=0–38). Median for HAMIS was of 6 (range=0–21) with Cronbach's alpha of 0.81; in test-retest: mean of the difference was of 0.091 (range= -5 to +5). Correlation between HAMIS and Cochin was significant (r=0.65; p=0.0002) Conclusions: An adapted Spanish version of HAMIS was developed, showing an acceptable reliability (Cronbach and stability) and criterion validity (correlation with Cochin test). Disclosure of Interest: None declared